Diversity of actinobacteria associated with Nostoc commune Vaucher ex Bornet & Flahault macrocolonies - Thanitsara Inthasotti (2018)
© 2015, Springer-Verlag Berlin Heidelberg and the University of Milan. Nostoc commune is a widely distributed freshwater cyanobacterium which grows on moist soil in Thailand, forming large or massive macroscopic colonies, called thallus, that are consumed as food by local people in the northeast region of Thailand. We have studied the diversity of actinobacteria associated with macroscopic thalli of N. commune using a 16S rRNA gene clone library. A total of 70 clones were sequenced, and 45 clones were found to cluster in ten actinobacterial families, namely, Microbacteriaceae, Dermacoccaceae, Pseudonocardiaceae, Intrasporangiaceae, Micrococcaceae, Solirubrobacteraceae, Corynebacteriaceae, Actinomycetaceae, Mycobacteriaceae, and Micromonosporaceae. The majority of the clones were closely related to Arthrobacter oryzae (5 clones, 11.1 %), Micrococcus endophyticus (4 clones, 8.9 %), and Pseudonocardia ailaonensis (4 clones, 8.9 %). Actinobacterial diversity was high, with a Shannon–Wiener index of 3.25 and a Chao1 index of 187.0 ribotypes with 71.11 % coverage. A total of 57 strains were isolated using 12 different media, and 43 isolates were selected for phylogenetic analysis on the basis of their 16S rRNA gene sequences. The results showed that these isolates belonged to six known genera, including Actinomadura, Arthrobacter, Gordonia, Rhodococcus, Sanguibacter, and Streptomyces. These results suggest that a diverse actinobacterial community is associated with macroscopic thalli of N. commune and that potential novel taxa may exist within this environment.